(untitled) (Orfeu, 2020)
This paper investigates the dialogical relations present in the compositional process of the orchestral piece Cada ano sem Debussy: dez versos sobre o seu nome (2019). It aims reflect on composition and concepts of musical utterance and dialogism under the light of Bakhtinian ideas. Based on three notions of dialogism (FIORIN, 2016) - constitutive, displayed and among individuals -, it examines how the musical work can be approached under these perspectives. For this, the analysis highlights the interaction between the authorial material and those by other ones used in the composition. It concludes that Bakhtin’s proposals can be effective tools of investigation in front of dialogical composition thinking.